2015
DOI: 10.1503/cjs.004014
|View full text |Cite
|
Sign up to set email alerts
|

The use of early immobilization in the management of acute soft-tissue injuries of the knee: results of a survey of emergency physicians, sports medicine physicians and orthopedic surgeons

Abstract: Background: Evidence-based guidelines on the use of immobilization in the management of common acute soft-tissue knee injuries do not exist. Our objective was to explore the practice patterns of emergency physicians (EPs), sports medicine physicians (SMPs) and orthopedic surgeons (OS) regarding the use of early immobilization in the management of these injuries. Methods:We developed a web-based survey and sent it to all EPs, SMPs and OS in a Canadian urban centre. The survey was designed to assess the likeliho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The results for the function and effect domain show that the Opencast ® provided somewhat less support than the conventional synthetic cast; however, there was no significant between-group difference in the amount of pain relief. The severity of pain experienced after an ankle sprain depended on the amount of inflammation present, which could be aggravated by movement of the injured tissues[ 11 , 12 ]. Therefore, this suggests that the injured ligamentous tissue was well protected and immobilized despite the patients’ subjective feelings otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…The results for the function and effect domain show that the Opencast ® provided somewhat less support than the conventional synthetic cast; however, there was no significant between-group difference in the amount of pain relief. The severity of pain experienced after an ankle sprain depended on the amount of inflammation present, which could be aggravated by movement of the injured tissues[ 11 , 12 ]. Therefore, this suggests that the injured ligamentous tissue was well protected and immobilized despite the patients’ subjective feelings otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…There was a lack of clear high‐level evidence on the best immobilisation strategy for specific knee injuries, advice on weight bearing and timing of commencement of range of motion exercises. A survey of emergency physicians, sports medicine physicians and orthopaedic surgeons on their practice patterns regarding the use of early immobilisation in common acute soft tissue injuries showed that emergency physicians were more likely to prescribe immobilisation than other specialties, demonstrating that there is variation in care between different health providers . Although complete knee joint immobilisation using either a splint or locked hinged brace may protect tissues and alleviate pain, there can be harmful effects of prolonged joint immobilisation such as joint stiffness and muscle atrophy .…”
Section: Discussionmentioning
confidence: 99%
“…70 Although complete knee joint immobilisation using either a splint or locked hinged brace may protect tissues and alleviate pain, there can be harmful effects of prolonged joint immobilisation such as joint stiffness and muscle atrophy. 41,70,71 Prescription of gentle range of motion exercises, basic quadriceps strengthening exercises and consideration for early follow up for rehabilitation and clinical review is essential to avoid any deleterious effects of prolonged immobilisation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limitation in the passive ROM of affected joints is termed a joint contracture, and this can be detrimental for joint performance. [1,2] The development of contractures can arise as a consequence of injury/disease (requiring extended periods of immobility), [2][3][4][5][6] or due to treatment (prolonged use of bracing). [7] The pathophysiology of joint contractures is progressive in nature, where increases in the duration of immobilization increases the severity of ROM loss.…”
Section: Introductionmentioning
confidence: 99%